(untitled) (Research, Society and Development, 2023)
This study presents a detailed investigation into cases of concurrent umbilical cord herniation and umbilical herniation in newborns. Through a descriptive and exploratory approach, the study examines clinical records, surgical reports, and medical literature to comprehend the clinical characteristics, adopted surgical procedures, and postoperative outcomes of these rare and complex cases. The literature review provides a solid foundation, while data analysis reveals patterns of presentation, varied surgical techniques, and post-surgical results. The study involves direct interventions on patients, focusing on a thorough understanding of these conditions. The results underscore the importance of meticulous analysis of these cases to guide future research and clinical practices, providing crucial insights for the medical community. This study significantly contributes to the knowledge about umbilical herniations and umbilical cord herniations in newborns, offering valuable recommendations for healthcare professionals in managing these complex conditions.